Increasing Shopper Trust in Retailer Technological Interfaces via Auditory Confirmation - Reynolds-McIlnay,Ryann; Morrin,Maureen (Journal of Retailing, 2019)
This research examines the effects of sounds made by retail technological interfaces – self- checkout kiosks, credit card readers, mobile apps, websites – at point-of-sale. We propose that such sounds, retail transaction auditory confirmation (RTAC), increase trust in technological interfaces by providing auditory confirmation that stages of the checkout process have been successfully executed. Increased trust in technological interfaces leads to positive downstream consequences in the form of satisfaction and purchase intention. Visual and auditory distraction in the retail environment reduces trust, even when visual confirmation is provided, but synchronously provided audio-visual confirmation attenuates the negative effects of environment distraction.
Keywords: Marketing